Ferrostatin-1 Ameliorates Liver Dysfunction via Reducing Iron in Thioacetamide-induced Acute Liver Injury in Mice - Jiang, Hui; Zhang, Xinyu; Yang, Wanping; Li, Meiqi; Wang, Guohua; Luo, Qianqian (Frontiers in Pharmacology, 2022)
Background and Aims: Hepatic iron overload always leads to oxidative stress, which has been found to be involved in the progression of liver disease. However, whether iron disorder is involved in acute liver disease and the further molecular mechanisms remain unclear. Methods：A mice model of acute liver injury (ALI) was established via intraperitoneal injection of thioacetamide (TAA) (250mg/kg/day) for 3 consecutive days. Ferrostatin-1 (Fer-1) was administered intraperitoneally (2.5 μM/kg/day) starting 3 days before TAA treatment. Deferoxamine (DFO) was intraperitoneally injected (200 mg/kg/day) with TAA treatment for 3 days. We further observed the effect of Fer-1 on TAA model with high-iron diet feeding. ALI was confirmed using histological examination and liver function activity. Moreover, expressions of iron metabolism and ferroptosis proteins were measured by Western blot analysis. Results: The study revealed that the iron accumulation and ferroptosis contributed to TAA-induced ALI pathogenesis. TAA induced prominent inflammation and vacuolar degeneration in the liver as well as liver dysfunction. In addition, protein expression of the cystine/glutamate antiporter SLC7A11 (xCT) and glutathione peroxidase 4 (GPX4) was significantly decreased in the liver, while transferrin receptor 1 (TfR1), ferroportin (Fpn) and light chain of ferritin (Ft-L) expression levels were increased after TAA exposure. As the same efficiency as DFO, pre-administration of Fer-1 signiﬁcantly decreased TAA-induced alterations in the plasma ALT, AST and LDH levels compared with the TAA group. Moreover, both Fer-1 and DFO suppressed TfR1, Fpn and Ft-L protein expression and decreased iron accumulation, but did not affect xCT or GPX4 expression in the liver. Both Fer-1and DFO prevented hepatic ferroptosis by reducing the iron content in the liver. Furthermore, Fer-1 also reduced iron and reversed liver dysfunction under iron overload conditions. Conclusion: These ﬁndings indicate a role of TAA-induced iron accumulation and ferroptosis in the pathogenesis of ALI model. The effect of Fer-1 was consistent with that of DFO, which prevented hepatic ferroptosis by reducing the iron content in the liver. Thus, Fer-1 might be a useful reagent to reverse liver dysfunction and decreasing the iron content of the liver may be a potential therapeutic strategy for ALI.